La competitividad como elemento esencial para el desarrollo de las regiones. Una mirada al Valle del Cauca (2011)
More and more regions are concerned to preserve and potentiate their resources, why competitiveness is a necessary framework to address those elements that are crucial for defining the prosperity of their society. This paper discusses the progress that the concept of competitiveness has been over time and also shows how in Colombia and the Cauca Valley approximations have been made about institutional and policy regarding the need to review to understand why competitiveness is not only one more term in the business world.